Situation Report: Czechoslovakia, 20 September 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The "Shield 72" Warsaw Pact Maneuvers New Management for Agriculture What Do Czechs Save For? Citizens Complaints